Complications Rate of Conventional Percutaneous Nephrolithotomy (PCNL) in a tertiary care center - Muhammad Asif, Khalid Farooq, Maryam Ikram Ullah, Akbar Azam, Romana Bibi, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To observe the complication rate of conventional percutaneous nephrolithotomy (PCNL) in a tertiary care Hospital. Methods: This Retrospective study conducted from January 2016 to January 2020 in the Department of Urology at Lady Reading Hospital in Peshawar, Pakistan.The research included a total of 449 patients who underwent conventional PCNL.Non-contrast CT KUB was performed on all patients before surgery. After passing 6fr Ureteric catheter through a cystoscope in lithotomy position patient was then shifted into prone position. Under the guidance of fluoroscopy, all procedures were carried out while the patient was lying flat and conventional 30FR amplatz sheath was used as working channel. Results: Complications were reported in 46.9% of cases.The majority of the complications occurred in patients with clavien grades I and II, with 120(27%) and 54(12%) patients, respectively. In Grade I complicationstransient feveroccurred in 67(15%) patients treated with antipyretics while 53(12%) patients had nephrostomy site leakage managed with simple pressure dressing at bed site. In grade II complication 45(10%) patients had bleeding which required transfusion and 9(2%) patients developed sepsis treated with parenteral antibiotics. 10(2%) patients developed grade IIIa complication such as persistent bleeding in 4(0.8%) patients managed with percutaneous angioembolization and 6(1.2%) patients required percutaneous drainage of perinephric collection. 25(5.5%) patients had grade IIIb complications, in 24( 5.3%) patients DJ stenting was done for PCS injury or persistent leakage from nephrostomy site while 1(0.2%) patient needed colostomy for colonic injury. Conclusion: The chance of serious complications during percutaneous nephrolithotomy is very minimal. It is also safe, cost effective and well-tolerated. Transient fever or nephrostomy site leakage are the most frequently occurring minor complications often subside spontaneously. Keywords: Nephrostomy, percutaneous nephrolithotomy